2021
DOI: 10.31261/tapsla.9993
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Using Corpus-Based Instructional Mediation on EFL Students’ Academic Writing Skills Improvement

Abstract: This study aimed at examining the effects of corpus-based instructional mediation on EFL learners’ academic writing skills improvement. To conduct the research, a quasi-experimental research design was employed. A total of 72 EFL mechanical engineering students participated in the study, and they were selected through a simple random sampling technique.  Among them, 25 students were assigned to the experimental group and 47 students to the control group. The data were gathered by means of pre- and post-tests. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This study showed that corpus use did not have an impact on improving learners' content, organization, and mechanics. The existing literature, on the other hand, provided evidence that corpora can be an effective reference tool for improving content and organization (Birhan et al, 2021), and punctuation marks (Celik & Ekatmis, 2013). The conflicting results could be derived from differences in the study designs, participant backgrounds, or the specific instructional methods employed in each study.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that corpus use did not have an impact on improving learners' content, organization, and mechanics. The existing literature, on the other hand, provided evidence that corpora can be an effective reference tool for improving content and organization (Birhan et al, 2021), and punctuation marks (Celik & Ekatmis, 2013). The conflicting results could be derived from differences in the study designs, participant backgrounds, or the specific instructional methods employed in each study.…”
Section: Discussionmentioning
confidence: 99%
“…The activities are designed from the corpus data that are assembled. Recently, researchers (e.g., Birhan, et al, 2021;Casan-Pitrach & Calvo-Ferrer, 2015;Huang, 2012) studied the impact of Birhan and Nurie Asian. J.…”
Section: Engagement In Academic Writing Classesmentioning
confidence: 99%
“…EFL writing classes have been characterized by the prevalence of teaching practices with less significant linguistic features that are not used frequently in their field of study, and these challenged learners to communicate effectively and construct various academic texts (Birhan et al, 2021). These indicate that the wrong teaching practices have contributed to the lack of engagement in the teaching-learning processes.…”
mentioning
confidence: 99%